2021
DOI: 10.3389/fspor.2021.657183
|View full text |Cite
|
Sign up to set email alerts
|

Intentions of Environmentally Friendly Behavior Among Sports Club Members: An Empirical Test of the Theory of Planned Behavior Across Genders and Sports

Abstract: Environmentally friendly behavior has become increasingly important in recent years to reduce the speed of climate change and its negative impacts. Individual behavior, including environmentally friendly behavior, is largely formed by behavioral intentions. This study draws on the theory of planned behavior to examine the effects of attitudes toward the behavior, subjective norms, and perceived behavioral control on intentions of environmentally friendly behavior. It also investigates differences between gende… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 67 publications
1
9
0
Order By: Relevance
“…Several studies show that there is need to treat males and females differently with regard to promoting positive intentions. In a study on environmentally responsible intentions across genders, it was revealed that behavioural intentions in women can be increased by increasing perceived behavioural control and subjective norms but not their attitudes (Braksiek et al, 2021). Another study found that consumption of environmentally friendly agricultural food was greater in females than in the male counter parts (Li et al, 2020).…”
Section: Mediating Role Of Behavioural Intentions To Eco-friendly Beh...mentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies show that there is need to treat males and females differently with regard to promoting positive intentions. In a study on environmentally responsible intentions across genders, it was revealed that behavioural intentions in women can be increased by increasing perceived behavioural control and subjective norms but not their attitudes (Braksiek et al, 2021). Another study found that consumption of environmentally friendly agricultural food was greater in females than in the male counter parts (Li et al, 2020).…”
Section: Mediating Role Of Behavioural Intentions To Eco-friendly Beh...mentioning
confidence: 99%
“…This implies that attitude and subjective norms are not the only antecedents of behaviour, but perceived behavioural control also plays a part. The power of each of these antecedents in affecting behavioural intentions depends on the situation and context (Braksiek et al, 2021). A study on behavioural intention in purchasing environmentally friendly agricultural food in China showed that subjective norms positively affect but attitude had no significant effect on the same (Li et al, 2020).…”
Section: Mediating Role Of Behavioural Intentions To Eco-friendly Beh...mentioning
confidence: 99%
“…The demographics section included gender, age, status, area of residence, education level, employment, total monthly household income, and the frequency of considering a sustainable product for use. Section two represented the latent variables of the STPB model [67][68][69][70][71][72][73][74][75][76][77][78][79][80], which are PI and PAS with (4) constructs each, CPV, SNs, AT, PBC, PENC, and PECC with (5) constructs each, to which all were taken from different studies shown in Table 1. The survey utilized 5 point-type Likert Scale (5 = strongly agree, 1 = strongly disagree) to evaluate the different constructs.…”
Section: Questionnairementioning
confidence: 99%
“…Environmental behavioral intention refers to the willingness of the individual to act and consume in a more sustainable manner. Environmentally friendly behavior is largely shaped by behavioral intentions (Braksiek et al, 2021). For Davis et al (2009), commitment to the environment is a very strong predictor of pro-environmental behavior.…”
Section: Environmental Behavior Changementioning
confidence: 99%